2023
DOI: 10.24996/ijs.2023.64.2.15
|View full text |Cite
|
Sign up to set email alerts
|

Photonic Crystal Fiber Pollution Sensor based on Surface Plasmon Resonance

Abstract: In this work, a pollution-sensitive Photonic Crystal Fiber (PCF) based on Surface Plasmon Resonance (SPR) technology is designed and implemented for sensing refractive indices and concentrations of polluted  water . The overall construction of the sensor is achieved by splicing short lengths of PCF (ESM-12) solid core on one side with traditional multimode fiber (MMF) and depositing a gold nanofilm of 50nm thickness on the end of the PCF sensor. The PCF- SPR experiment was carried out with various samples of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Beam divergence is a parameter that assessed the light beam quality and the angle of divergence of the beam from a straight path. Beam divergence is calculated from equation (9) and equation (10) that is directly related to the spot size. Figure 11 represents the relationship between the beam divergence and operating wavelength from 1.6 to 4.0 μm for the proposed PCF sensor with the selected food additive analytes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Beam divergence is a parameter that assessed the light beam quality and the angle of divergence of the beam from a straight path. Beam divergence is calculated from equation (9) and equation (10) that is directly related to the spot size. Figure 11 represents the relationship between the beam divergence and operating wavelength from 1.6 to 4.0 μm for the proposed PCF sensor with the selected food additive analytes.…”
Section: Resultsmentioning
confidence: 99%
“…Photonic Crystal Fibres (PCFs), recently, have been utilised in sensing applications, other than their common use in optical communication, imaging, and many more [1][2][3]. PCFs have been implemented to measure and detect temperature, chemicals, pressure, liquid, gas, and so on [4][5][6][7][8][9][10]. Current research has revealed that certain food additives can cause long-term effects on humans.…”
Section: Introductionmentioning
confidence: 99%
“…To detect the absorption of various compounds on metal films, such as gold (Au) and silver (Ag), SPR sensors employ a variety of devices. Drug discovery, environmental protection, and medical diagnostics are all areas where this technique is useful [29][30][31][32]. The investigation of positioner surface plasmon produced by light oscillations of conduction band electrons in metal nanoparticles led to a significant improvement in characteristics.…”
Section: Introductionmentioning
confidence: 99%